Genetic parameters and trends of growth traits in Nelore cattle raised in the Northern region of Brazil - Rodrigues, Mariana Rocha; Espigolan, Rafael; Ferraz, José Bento Sterman; Bussiman, Fernando Oliveira; Toniolli, Ricardo; Lôbo, Raysildo Barbosa; Santos, Helcileia Dias; Nepomuceno, Leandro Lopes; Ferreira, Jorge Luís (Brazilian Journal of Veterinary Research and Animal Science, 2022)
The objective of this study was to estimate (co)variances and genetic parameters and to predict genetic trends for weight at 120 (W120), 210 (W210), 365 (W365), and 450 (W450) days of age in Nelore cattle raised in the northern region of Brazil. The database comprised records of 30,387 animals born between 2000 and 2013 in the Brazilian North. Estimates were calculated by the Restricted  Maximum Likelihood (REML) method, in single- and multi-trait analyses in an animal model. Heritability as obtained using single- and multi-trait models for W120 (0.22 and 0.31), W210 (0.20 and 0.34), W365 (0.51 and 0.51), and W450 (0.49 and 0.51) indicated moderate to high magnitudes, with the possibility of genetic selection and incorporation into the herd. Genetic correlations between growth traits were favorable, ranging from 0.78 to 0.96. Genetic trends for W120 and W210 varied largely, from -0.31 to 4.68 and -0.53 to 7.62 kg/year, respectively. Smaller fluctuations were observed in genetic trends for W365 and W450, which ranged from -1.08 to 10.90 and -1.29 to 12.51 kg/year, respectively. Selection for W365 and W450 proved to be the criterion of choice for Nelore herds raised in the region; however, it may compromise adult performance because of higher costs and time for production. A thorough analysis of mattings is recommended to allow the selection of earlier-developing animals.